Echocardiographic features of free floating thrombus mimicking right ventricular myxoma. Issue 6 (June 1983) - Shiu, M F; Abrams, L D
Abstract : M-mode and cross-sectional echocardiography performed in a patient with acute pulmonary embolism showed a sausage shaped, mobile mass in the right ventricular cavity highly suggestive of a right ventricular myxoma. Emergency thoracotomy 24 hours later showed the right ventricle to be free of tumour but both pulmonary arteries contained embolised venous thrombi, one or more of which were thought to have given rise to the false echocardiographic diagnosis of a right ventricular tumour.